Mysterious Association of Systemic Lupus Erythematosis with Perry Romberg Syndrome - Marium Kanwal, Shafique Rehman Arain, Rabab Qazi, Soha Samreen, Ayesha Murtaza, Hareer Fatima, Hussain Sohail Rangwala (Pakistan Journal of Medical & Health Sciences, 2023)
Parry Romberg syndrome (PRS), also referred to as progressive hemifacial atrophy, progressive facial hemiatrophy, or idiopathic hemifacial atrophy, was first described by C Parry and M Romberg.1 It manifests in the first two decades in morphologically normal-born individuals. It commonly affects one or more dermatomes in the trigeminal nerve territory. It has an early onset of ophthalmic and neurological involvement and a variable maxillo-facial or cardiac involvement. It is an idiopathic, gradually progressive craniofacial asymmetry, following the atrophy of subcutaneous tissue, muscles, osseous, and cartilaginous structures. Ophthalmic involvement occurs in up to 35% of cases2. Neurological symptoms manifest in 15 to 20% of cases3.